Cortical bone adaptation and mineral mobilization in the subterranean mammal Bathyergus suillus (Rodentia: Bathyergidae): effects of age and sex - Montoya-Sanhueza,Germán; Chinsamy,Anusuya (PeerJ, 2018)
The patterns of bone modeling and mineral mobilization (skeletal homeostasis) among mammals other than humans and laboratory rodents are still poorly known. In this study we assessed the pattern of bone formation and bone resorption in the femur of a wild population of Cape dune molerats, Bathyergus suillus (n = 41) (Bathyergidae), a solitary subterranean mammal with a marked extended longevity among rodents, and which also lives in a naturally deficient state of vitamin D. In order to determine ontogenetic and sex effects on histomorphometric parameters of transversal undecalcified bone sections, two-way ANOVA, linear mixed-effects model and regression statistical analyses were performed. During ontogeny, B. suillus increased their cross sectional area, cortical area and cortical thickness, and most importantly, they showed scarce endosteal bone resorption which resulted in a retained medullary cavity size during ontogeny. This resulted in a positively imbalanced bone modeling, where bone formation considerably surpasses bone loss by almost 100-fold in adulthood. This differs markedly from other terrestrial mammals with relatively thin cortical walls. Regarding bone loss and remodeling, three main processes involving intracortical resorption were observed: modeling-related bone loss in early postnatal growth; secondary osteon formation occurring in both sexes; and subendosteal secondary reconstruction observed only in females. The latter is accompanied by females having six-fold more relative bone loss than males, which is evidenced by the development of enlarged resorption cavities (RCs) distributed circumferentially around the medullary cavity. Males have smaller, more circular and randomly distributed RCs. In general, our data indicate no age-related decline in mineral content in B. suillus, and provides strong support for a pattern of sexual dimorphism in skeletal homeostasis, similar to that occurring in humans and other mammals, with females losing more bone throughout aging as compared to males due to reproductive factors. Interestingly as well, despite the high mechanical loads experienced during burrow construction, bone remodeling in B. suillus is kept at very low levels throughout their lifespan, and dense Haversian tissue never forms. This study represents the first comprehensive assessment of skeletal homeostasis in a subterranean mammal, and it enables a better understanding of the complex processes governing the acquisition and maintenance of bone properties in this species with extraordinary fossorial adaptations.
Keywords: Intracortical porosity; Skeletal homeostasis; Histomorphometry; Sexual dimorphism; Cortical bone; Resorption cavities; Fossorial adaptations; Bone microstructure; Bone compactness